An Environmental Analysis of Reusable and Disposable Surgical Gowns. (4th March 2020) - Vozzola, Eric; Overcash, Michael; Griffing, Evan
ABSTRACT: Surgical gowns help protect patients from exposure to microorganisms and serve as personal protective equipment for perioperative staff members. Medical textiles, including surgical gowns, are available as reusable and disposable products. Health care facility administrators and leaders who endeavor to use environmentally sustainable practices require current data for decision making. This study analyzed all activities from the extraction of fossil materials from the earth to the end‐of‐life disposal of reusable and disposable surgical gowns. The researchers included calculations for laundry and wastewater treatment operations and compared the environmental effects of the two surgical gown systems. The study results showed that selection of reusable gowns rather than disposable gowns reduced natural resource energy consumption (64%), greenhouse gas emissions (66%), blue water consumption (83%), and solid waste generation (84%). Perioperative nurses can use this information to assist facility leaders as they make informed decisions related to gown system selection.